Absence of JAK2V617F Mutated Endothelial Colony-Forming Cells in Patients With JAK2V617F Myeloproliferative Neoplasms and Splanchnic Vein Thrombosis. Issue 3 (5th June 2020) - Guy, Alexandre; Danaee, Anicee; Paschalaki, Koralia; Boureau, Lisa; Rivière, Etienne; Etienne, Gabriel; Mansier, Olivier; Laffan, Michael; Sekhar, Mallika; James, Chloe
Abstract : Supplemental Digital Content is available in the text